2020
DOI: 10.7759/cureus.7190
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Advanced Cardiac Life Support Simulation Training on Medical Student Self-reported Outcomes

Abstract: Introduction: Simulation has become a well-recognized and innovative tool in medical education. While there has been tremendous growth of simulation curricula at the level of graduate medical education, there have been few studies looking at simulation as a learning tool for undergraduate medical education. The goal of this study was to determine if highfidelity simulation training impacts medical student perception of knowledge and confidence regarding comprehension and application of advanced cardiac life su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Personal confidence in their ability to perform as a nurse plays an influential role in the transition from new nurses to seasoned nurses. Many newly licensed nurses may lack confidence in their nursing skills, ability to communicate with physicians, clinical decision-making, and priority-setting (Bowers et al, 2020). The literature strongly supports the use of simulation to increase the confidence levels of participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Personal confidence in their ability to perform as a nurse plays an influential role in the transition from new nurses to seasoned nurses. Many newly licensed nurses may lack confidence in their nursing skills, ability to communicate with physicians, clinical decision-making, and priority-setting (Bowers et al, 2020). The literature strongly supports the use of simulation to increase the confidence levels of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach's alphas were 0.93 on pre-test and 0.96 on post-test, indicating high internal consistency and reliability. Hart et al (2014) found that higher self-confidence levels were associated with better skill performance and clinical decision-making.…”
Section: Findings From the Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16] This study focused on those about to enter an emergency medicine residency program, but there are several other documented studies where the use of simulation has positively impacted the confidence of a broader range of students. 3,4,[17][18][19][20] Simulation has been established as a successful, evidence-based tool in medical education for several decades. 8,21 Simulation use in emergency medicine education -both in medical schools and residency programs -has become widespread in the last 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation tends to be especially helpful in establishing a constructive scenario for medical students to practise their skills. [4,5] Simulation provides a safe learning environment, without fear of causing clinical harm and perceived associated blame, thus producing a relaxed and encouraging environment to learn particularly challenging skills. Our results prove that simulation is a reliable method to increase confidence and performance in the resuscitation of patients in the EM department.…”
Section: Discussionmentioning
confidence: 99%